2017
DOI: 10.1002/we.2126
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid vortex simulations of wind turbines using a three‐dimensional viscous–inviscid panel method

Abstract: A hybrid filament‐mesh vortex method is proposed and validated to predict the aerodynamic performance of wind turbine rotors and to simulate the resulting wake. Its novelty consists of using a hybrid method to accurately simulate the wake downstream of the wind turbine while reducing the computational time used by the method. The proposed method uses a hybrid approach, where the near wake is resolved by using vortex filaments, which carry the vorticity shed by the trailing edge of the blades. The interaction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 28 publications
0
54
0
Order By: Relevance
“…Time ratios can vary from one computer system to another, and they depend on the number of blade elements/stations, enabled DOFs and other inputs that affect the number of calculations per time step, see, e.g., Section 4.1. In particular, MIRAS contains several parameters to control the computational speed and accuracy of the wake, which has not been investigated in the current study. Figure depicts the percent difference in torque and thrust relative to one‐to‐one coupling (left) and time ratios (right) versus the time step.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Time ratios can vary from one computer system to another, and they depend on the number of blade elements/stations, enabled DOFs and other inputs that affect the number of calculations per time step, see, e.g., Section 4.1. In particular, MIRAS contains several parameters to control the computational speed and accuracy of the wake, which has not been investigated in the current study. Figure depicts the percent difference in torque and thrust relative to one‐to‐one coupling (left) and time ratios (right) versus the time step.…”
Section: Resultsmentioning
confidence: 99%
“…The accuracy of the loads computed on the rotor is dependent on the wake resolution, see Ramos‐García et al . and Ramos‐García et al . for details.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MIRAS is a multi‐fidelity computational vortex model mainly used for predicting the aerodynamic behavior of wind turbines and its wakes. It has been developed at Technical University of Denmark (DTU) during the last decade, and it is extensively validated for small to large size wind turbine rotors by Ramos‐Garcia et al…”
Section: Methodology For Validationmentioning
confidence: 99%
“…To avoid the singular behavior of newly released vortex elements, an initial core radius, ε0, is introduced. In accordance with Ramos‐Garcia et al, where it was found out that a small core radius is necessary to have flow convergence, a core radius of 0.1% local chord at the release station is used.…”
Section: Methodology For Validationmentioning
confidence: 99%